Infertility Treatment and Umbilical Cord Length–Novel Markers of Childhood Epilepsy? - Räisänen, Sari (Public Library of Science, 2013)
BACKGROUND: Epilepsy is one of the most common neurologic disorders of childhood, affecting about 0.4−0.8% of all children up to the age of 20. METHODOLOGY: A population-based retrospective cohort study. Aim was to determine incidence and identify perinatal and reproductive risk factors of epilepsy in children born between 1989 and 2008 among women (n = 43,389) delivered in Kuopio University Hospital. Risk factors of childhood epilepsy were determined by using logistic regression analysis. PRINCIPAL FINDINGS: The incidence of childhood epilepsy was 0.7% (n = 302 of 43,389). Maternal epilepsy, major congenital anomalies and use of assisted reproductive technology (ART) were associated with 4.25-, 3.61-, and 1.67- fold increased incidence of childhood epilepsy. A 10 cm increase in umbilical cord length was associated with a 15% decrease in the incidence of epilepsy (adjusted OR 0.85, 95% CI 0.78−0.94). However, the above reproductive factors accounted for less than 2% of total incidence, whereas maternal epilepsy proved to be the highest risk factor. CONCLUSIONS: Perinatal and reproductive factors were shown to be minor risk factors of childhood epilepsy, implying that little can be done in obstetric care to prevent childhood epilepsy. Infertility treatment and umbilical cord length, independent of gestational age and congenital malformations, may be novel markers of childhood epilepsy.